Emotional processing in obsessive-compulsive disorder - Casado-Martín, Yolanda; Cobos-Álvarez, María del Pilar; Machado-Pinheiro, Walter; Vila, Jaime (Elsevier, 2011)
The aim of the present study was to investigate whether there are differences in emotional processing among people with obsessive–compulsive disorder, using Lang's dimensional model of emotions. A total of 22 individuals with obsessive–compulsive disorder participated in the study and were compared to a control group (n = 25). All participants assessed a set of photographs with emotional content (pleasant, neutral, unpleasant, and with obsessive–compulsive content) using the Self-Assessment Manikin pictorial scales for rating emotional valence (pleasant/unpleasant), arousal (calm/aroused) and dominance (controlling/controlled). The results show significant differences in the processing of emotional images among individuals with obsessive–compulsive disorder and the high predictive value of dominance for diagnosis.
Keywords: Personalidad - Trastornos; Obsessive–compulsive disorder; Emotion; Affective picture processing; Emotional dominance